1930
DOI: 10.1098/rspb.1930.0054
|View full text |Cite
|
Sign up to set email alerts
|

The distillation of vitamin D

Abstract: The work described below has been done in an attempt to isolate vitamin D from the complex mixture formed by the ultra-violet irradiation of ergosterol. It is evident that vacuum distillation might be of use for this purpose, but, except for a brief statement by Windaus and Holtz (1927), we are unaware of previous work on the distillation of vitamin D.We have distilled various products obtained from ergosterol, and most frequently have used resinous products prepared as follows. A solution of ergosterol in eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0
3

Year Published

1930
1930
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(29 citation statements)
references
References 2 publications
1
25
0
3
Order By: Relevance
“…40 Na mesma época, Hulshinsky 41 observou que crianças expostas à radiação solar ou artificial ultravioleta apresentavam melhora do raquitismo. Em 1931, Askew et al 42 identi-ficaram a estrutura molecular da "vitamina D2" (ergocalciferol). Windaus, 43,44 que erroneamente havia identificado a estrutura da "vitamina D1", acabou conseguindo descrever corretamente a estrutura da "vitamina D3".…”
Section: Doenças óSseas Risco De Queda E Fraturasunclassified
“…40 Na mesma época, Hulshinsky 41 observou que crianças expostas à radiação solar ou artificial ultravioleta apresentavam melhora do raquitismo. Em 1931, Askew et al 42 identi-ficaram a estrutura molecular da "vitamina D2" (ergocalciferol). Windaus, 43,44 que erroneamente havia identificado a estrutura da "vitamina D1", acabou conseguindo descrever corretamente a estrutura da "vitamina D3".…”
Section: Doenças óSseas Risco De Queda E Fraturasunclassified
“…The measurements of absorption spectra, and of antirachitic activity were made by the methods described in our paper on the Distillation of Vitamin D (Askew et al, 1930).…”
Section: Technique Of Measurement and Of Irradiationmentioning
confidence: 99%
“…Hess et al (1925) and Steenbock and Black (1926) showed that ultraviolet light induced antirachitic activity in the sterol fraction of biological material. The formation of vitamin D2 from ergosterol was shown by Askew et al (1931), while Windaus et al (1936) demonstrated the formation of vitamin D3 from 7-dehydrocholesterol.…”
mentioning
confidence: 99%